Amino acids and protein profiles of defatted camel and cow milk fractions: correlation with their in vitro antioxidant and antidiabetic activities - Harizi, Nouha; Zouari, Ahmed; Rokbeni, Nesrine; Ben Zid, Malek; M’hiri, Nouha; Salem, Ali; Ayadi, Mohamed Ali; Boudhrioua, Nourhene (Frontiers in Nutrition, 2024)
This work presents proteins, amino acids profiles and antioxidant (DPPH radical scavenging activity) and antidiabetic (in vitro α-amylase inhibitory activity) properties of camel and cow milk fractions produced using an integrated coagulation-centrifugation process. Antioxidant and antidiabetic activities were assessed on defatted milk fractions and their extracts using water/ethanol or HCl/ethanol solvents. The predominant protein found in cow and camel milk was β-casein in sodium caseinate, β-lactoglobulin was found in the whey of cow milk, whereas α-lactalbumin was detected in the whey fractions of camel. The primary amino acids (comprising 1% to 5.2%) in skim milk and sweet whey milk were leucine, proline, and lysine. However, acid whey, casein fractions (sodium caseinate, and β-casein) from both camel and cow milk exhibited elevated concentrations of histidine, leucine, lysine and proline (1.12 – 6.62%). Camel milk and its different protein fractions showed an interesting in vitro α-amylase inhibitory activity varying, according to different milk fractions and extraction methods, from 19.10 ± 1.40 to 97.40 ± 1.50%. Whatever the used method, the whey fractions from camel milk, both acid and sweet, demonstrated the most promising antioxidant activity. Sweet and acid cow milk fractions seem to be the most promising for deeper exploration of in vivo biological activities and are promising milk derivatives for specific nutritional diet and/or functional food formulation. Principal components analysis showed a positive correlation between the total phenols content, antioxidant (DPPH assay) and antidiabetic (α amylase inhibition test) activities within the milk fractions.